Smart farm and poultry that automatic working with sensor and can control with smartphone - สมทรง, ปวิชญา; คนึงคิด, สรณ์สิริ; บรรดาศักดิ์, สุพาพร (Rattanakosin Journal of Science and Technology, 2021)
IOT or Internet of thing means that devices and things are connected to the Internet. Allows humans to control the use of various devices via the Internet, such as turning on-off electronic devices in home or sensors used to control various devices. from the research of articles about Smart Farm. Application of Internet of thing technology to solve problems related to smart farm systems. The temperature and humidity problems that affect productivity and disease of chickens. With good temperature and humidity control, yields can be controlled most effectively. Controlling various sensors can be done quickly and easily by connecting the system to the Internet and the Mobile Application to achieve consistent control.